Pengaruh Dosis Urea terhadap Jerapan Ammonium dan Nitrat pada Biochar Sekam - Chandra, Kartika Ferina; Kesumadewi, A.A. Istri; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024)DO - 10.24843/AJoAS.2024.v14.i01.p08, 2024)
Effect of Urea Dosage on Ammonium and Nitrate Absorption by Rice Husk Biochar. Biochar is a biological charcoal which is rich in carbon and functional groups, thus it capable to absorb nutrients including nitrate and soil ammonium which comes from ammonification and nitrification of urea. Activated rice husk biochar enriched with urea doses of 0:100, 50:50; 25:75 (percentage of biochar:urea; w/w) was tested for its ability to adsorb ammonium and nitrate through laboratory research. Each measurement was carried out weekly from 0-35 days with 3 replications. The results showed that the activated rice husk biochar able to absorb ammonium. Higher absorption was obtained in urea treatment with higher doses, namely 75 and 100% urea. A better incubation time to enrich rice husk biochar was 14 days for urea levels of 50 or 75%. The optimal ammonium uptake for the 50% urea + 50% rice husk biochar treatments were 489.83 mg.kg-1 and 482.80 mg.kg-1 for the 75% urea + 25% rice husk biochar treatment. The absorbed nitrate levels in the two treatments were 251.85 and 189.62 mg.kg-1 respectively. These findings can be a reference for determining the time needed to enrich rice husk biochar with urea to reduce the potential loss of nitrogen from urea hydrolysis. It is recommended to study activation materials that are more environmental-sound and determine the optimal proportions of urea and biochar in biochar.